pyrG of Aspergillus nidulans, meiotic mapping, marker interactions and growth response - E. Käfer; G. May (Fungal Genetics Reports, 1988)
Information of the genetic location of pyrG and its growth response under various conditions has become important with the recent cloning of pyrG (Oakley et al. 1987. Gene 61:385-399) and with the use of pyrG strains as recipients for transformation when pyr-4 cloning vectors are used for A. nidulans libraries (e.g. May et al. 1985 J. Cell Biol. 101:712-719 ; Osmani et al. 1987 J. Cell Biol. 104:1495-1504).